GLUT1 inhibition blocks growth of RB1-positive triple negative breast cancer - Qin Wu (Nature Portfolio, 2020)
Triple negative breast cancer is a deadly form of breast cancer with limited therapeutic options. Here the authors show the efficacy of GLUT1 pharmacological inhibition against a subset of tumors expressing RB1, thereby identifying RB1 protein level as a biomarker of sensitivity to anti-GLUT1 therapy.